1987
DOI: 10.1128/aem.53.12.2914-2921.1987
|View full text |Cite
|
Sign up to set email alerts
|

Tests of the Critical Assumptions of the Dilution Method for Estimating Bacterivory by Microeucaryotes

Abstract: The critical assumptions of the dilution method for estimating grazing rates of microzooplankton were tested by using a community from the sediment-water interface of Lake Anna, Va. Determination of the appropriate computational model was achieved by regression analysis; the exponential model was appropriate for bacterial growth at Lake Anna. The assumption that the change in grazing pressure is linearly proportional to the dilution factor was tested by analysis of variance with a lack-of-fit test. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 43 publications
0
10
1
1
Order By: Relevance
“…We have shown how the study of Andersen et al (199 1) can be made more general by the use of growth equations incorporating feeding saturation and nonlinear regression techniques. This extends the utility of this protocol because such nonlinear grazing functions are commonly encountered (Tremaine and Mills 1987;Gallegos 1989;Evans and Paranjape 1992;Elser and Frets 1995). Future use of this methodology should maximize statistical power by relying on a larger number of dilution steps than we attempted here and, with experience, choosing dilution steps that emphasize portions of the growth curves where the largest changes in growth as a function of dilution are expected.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…We have shown how the study of Andersen et al (199 1) can be made more general by the use of growth equations incorporating feeding saturation and nonlinear regression techniques. This extends the utility of this protocol because such nonlinear grazing functions are commonly encountered (Tremaine and Mills 1987;Gallegos 1989;Evans and Paranjape 1992;Elser and Frets 1995). Future use of this methodology should maximize statistical power by relying on a larger number of dilution steps than we attempted here and, with experience, choosing dilution steps that emphasize portions of the growth curves where the largest changes in growth as a function of dilution are expected.…”
Section: Discussionmentioning
confidence: 67%
“…Although we did not measure DOC in our treatments, we can state that amendments with N and P caused increased growth relative to control treatments and the presence of algal competitors lowered bacterial growth (Chrzanowski et al 1995), weakening the case for DOC limitation of bacteria because algae are sources, not sinks, for this resource. Others (Tremaine and Mills 1987) have also concluded that substrate enrichment is unlikely to be important in experiments such as these. The question of substrate enrichment in the partitioning of nutrient sources is more problematic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Least-squares regressions (40) were conducted on logarithmically transformed bacterial concentration-versus-time plots (69) to estimate bacterial apparent specific growth rates in the presence (r,) and relative absence (rd) of grazing (76).…”
Section: Methodsmentioning
confidence: 99%
“…Thí nghiệm nuôi pha loãng được tiến hành theo Landry & Hassett (1982) [12]Tremaine & Mills (1987) [26]. Kỹ thuật này bao gồm việc pha loãng toàn bộ quần xã sinh vật phù du (SVPD) với nước biển đã được lọc (thường là qua màng 0,2 µm) theo các nồng độ giảm dần để tạo ra các mức độ bắt gặp khác nhau giữa nhóm sinh vật ăn mồi và con mồi, trong khi tốc độ tăng trưởng của con mồi được mặc định như nhau.…”
Section: Thiết Kế Thí Nghiệm Nuôi Pha Loãng Và Tính Toánunclassified